Analisis Penerapan Etika Bisnis Islam Dalam Komunikasi Pemasaran Produk Simpanan Simbakota di BMT Dana Mentari Muhammadiyah Purwokerto - Sulasih, Sulasih; Novandari, Weni; Setyanto, Refius Pradipta (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
BMT Dana Mentari Muhammadiyah Purwokerto Karanglewas Service Office presents the SIMBAKOTA savings product which aims to meet customers' basic needs on Eid. In marketing SIMBAKOTA products, of course, it is adapted to Islamic business ethics and marketing communications in order to create good service to customers so that it can increase the number of customers and income every year. This research is field research using a qualitative approach method with descriptive analysis. The results of this research have implemented Islamic business ethics in running its business by prioritizing the values of monotheism, balance, free will, responsibility and ihsan. As well as its relationship with marketing communications in accordance with good marketing principles which pay attention to the principles of advertising, personal selling, sales promotion, public relations and publicity